2013
DOI: 10.1002/jbm.b.33090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biocompatibility and degradation of chitosan nanofiber membrane crosslinked with genipin

Abstract: Chitosan, a natural polysaccharide, has demonstrated potential as a degradable biocompatible guided bone regeneration membrane. This study aimed to evaluate the in vivo biocompatibility and degradation of chitosan nanofiber membranes, with and without genipin crosslinking as compared with a commercial collagen membrane in rat model. Chitosan nanofiber membranes, with and without genipin crosslinking, and collagen membrane (control) were implanted subcutaneously in the backs of 30 rats. The membranes were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 40 publications
(168 reference statements)
3
22
0
Order By: Relevance
“…CS has excellent biocompatibility and has been approved by the US Food and Drug Administration and the European Medicines Agency for biomedical applications in the human body (Dornish, Kaplan, & Arepalli, ). The results in Figure (b, c) are consistent with previous in vitro and in vivo studies where the biocompatibility of genipin cross‐linked CS and PPY was confirmed (Bavariya et al, ; Chen et al, ; Vaitkuviene et al, ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…CS has excellent biocompatibility and has been approved by the US Food and Drug Administration and the European Medicines Agency for biomedical applications in the human body (Dornish, Kaplan, & Arepalli, ). The results in Figure (b, c) are consistent with previous in vitro and in vivo studies where the biocompatibility of genipin cross‐linked CS and PPY was confirmed (Bavariya et al, ; Chen et al, ; Vaitkuviene et al, ).…”
Section: Resultssupporting
confidence: 90%
“…The in vitro degradation profiles of the scaffolds in PBS containing 10 μg/ml lysozyme at 37 °C are shown in Figure a. After 10 weeks, the CS scaffold lost 20% of its original weight; degradation is predominantly via lysozyme‐induced hydrolysis of glycosidic linkages (Bavariya et al, ). For the PPY/XCS scaffold, 15% weight loss was observed after 10 weeks of incubation; this degradation profile is considered acceptable as ES treatment for bone healing usually lasts for less than 3 months (Goldstein, Sprague, & Petrisor, ).…”
Section: Resultsmentioning
confidence: 99%
“…This may contribute to improved resistance in enzymatic degradation especially for the cases of higher concentrations of GP were used for crosslinking the nanofibrous CTS. Our observation is in accordance with previously reported decrease in CTS degradation due to the GP-crosslinking of CTS (Bavariya et al, 2014;Mi et al, 2001).…”
Section: In Vitro Enzymatic Degradationsupporting
confidence: 95%
“…8. MTT assay of L929 fibroblasts cultured on nanofibrous CTS scaffold, GP (0.1%, 0.5% and 1%) crosslinked nanofibrous CTS scaffolds, and tissue culture plate (TCP) after culturing for 1, 4 and 7 d. * Indicates P < 0.05 and ** indicates P < 0.01. responses as compared with the commercial collagen membrane in rat model (Bavariya et al, 2014). Thus, our current in vitro cytocompatibility results are in agreement with other groups reported that incorporation of GP improved the biocompability of various CTS formulations (Yan et al, 2010).…”
Section: Viability Of Fibroblast Cells On Gp-crosslinked Nanofibrous supporting
confidence: 95%
See 1 more Smart Citation